Enhancing marketing performance in batik Malay industry: optimization competitive advantage by leveraging augmented reality marketing - Annisa Mardatillah; Lilis Marina Angraini; Sri Yuliani (Cogent Business & Management, 2024)
This study aims to explore how augmented reality (AR) and a company's unique resources optimize competitive advantage to improve marketing performance using a qualitative approach with triangulated in-depth interviews. The findings of this study revolve around three main themes: improving marketing performance, improving competitiveness, and strengthening customer relationships. The results show that AR in this study provides unique added value that is different from competitors and strengthens deeper interactions between batik products and customers. The theoretical contribution of this study connects the Resource Based View (RBV) theory with the application of augmented reality to the marketing of small and creative traditional batik industries, connecting unique resources, namely the cultural value of batik products, to improve marketing performance through optimizing competitive advantages, thereby strengthening relationships with customers. Intangible assets such as customer relationships are optimized for competitiveness and marketing performance optimization. In addition, this study provides practical implications for practitioners in the batik industry to utilize AR as an effective marketing tool to assist in making strategic decisions regarding technology investment and product development to improve marketing performance through optimizing its resources for competitiveness.
Keywords: 650; Augmented reality marketing; competitive advantage; performance; customer experience; digital marketing